Sherman Alexie’s Version and Subversion of Native American Storytelling Tradition - Knežević, Marija (American & British Studies Annual, 2010)
Sherman Alexie understands writing as a means of fighting for the cultural identity of the American Natives against the dominant culture and also against the social compliance and lethargy of his own people. Since for him literature equals rage and imagination, the task of an artist is to be loud, poetic, cruel and inappropriate, in other words, to undermine mythologies. This assumption results in cruelly realistic work, for which reason Alexie is controversial. To non-native readers his voice is surprising and entertaining, but native readers often passionately disapprove of the images of natives Alexie depicts, as well as his distortion of the traditional narrative voice and its sacred function. What seems, however, to be the least traditional feature of Alexie’s work, an abundance of markers of popular culture, strikes me as a potent, though discomforting, challenge, inviting the reader, as good storytelling always does, to participate in the construction of meaning of our mutual present.